Taxonomic composition and carbohydrate-active enzyme content in microbial enrichments from pulp mill anaerobic granules after cultivation on lignocellulosic substrates - Wong, Mabel T.; Nesbø, Camilla L.; Wang, Weijun; Couturier, Marie; Lombard, Vincent; Lapebie, Pascal; Terrapon, Nicolas; Henrissat, Bernard; Edwards, Elizabeth A.; Master, Emma R. (Frontiers in Microbiomes, 2023)
Metagenomes of lignocellulose-degrading microbial communities are reservoirs of carbohydrateactive enzymes relevant to biomass processing. Whereas several metagenomes of natural digestive systems have been sequenced, the current study analyses metagenomes originating from an industrial anaerobic digester that processes effluent from a cellulose pulp mill. In particular, the community composition and profile of predicted carbohydrate-active enzymes were analyzed following anaerobic cultivation of the digester inoculum on cellulose and pretreated (steam exploded) poplar wood chips. Recognized lignocellulose degraders were abundant in the resulting cultures, including populations belonging to Clostridiales and Bacteroidales orders. Poorly defined taxonomic lineages previously identified in other lignocellulose-degrading communities were also detected, including the uncultivated Firmicutes lineage OPB54 which represented nearly 10 % of the cellulose-fed enrichment even though it was not detected in the bioreactor inoculum. In total, 3580 genes encoding carbohydrate-active enzymes were identified through metagenome sequencing. Similar to earlier enrichments of animal digestive systems, the profile encoded by the bioreactor inoculum following enrichment on pretreated wood was distinguished from the cellulose counterpart by a higher occurrence of enzymes predicted to act on pectin. The majority (> 93 %) of carbohydrate-active enzymes predicted to act on plant polysaccharides were identified in the metagenome assembled genomes, permitting taxonomic assignment. The taxonomic assignment revealed that only a small selection of organisms directly participates in plant polysaccharide deconstruction and supports the rest of the community.